Development of Functional Competence in English Language Lessons - Procházková, Natálie (Univerzita Pardubice, 2020)
This bachelor thesis focuses on the definition of functional competence in English language teaching as well as on its occurrence in a chosen textbook. The practical part deals with the concepts of functional competence in spoken language and it defines the didactic opportunities for its development with respect to the characteristics of interactions that are functionally specified. The aim of the practical section is to analyse given didactic tools and to determine whether they provide activities that help develop functional competence by set criteria.
Rozvoj funkční kompetence ve výuce anglického jazyka
Keywords: functional competence; upper-secondary level; speaking; evaluation of a textbook; funkční kompetence; středoškolský stupeň; mluvený projev; hodnocení učebnice